18[F]FDG-PET/CT is a useful molecular marker in evaluating tumour aggressiveness: a revised understanding of an in-vivo FDG-PET imaging that alludes the alteration of cancer biology - Ahmad Saad, Fathinul Fikri; Nordin, Abdul Jalil; Lau, W. F. E. (Springer, 2013)
Molecular imaging employing 18 [F] FDG-PET/CT enables in-vivo visualization, characterisation and measurement of biological process in tumour at the molecular and cellular level. In oncology, this approach can be directly applied as translational biomarkers of disease progression. In this article, the improved roles of FDG as an in-vivo glycolytic marker which reflect biological changes across in-vitro cellular environment are discussed.